A National Primary PCI Network in Libya: An Urgent Health Policy Imperative - Ali M. Elneihoum, MD, PhD, FESC (Benghazi University Medical Journal, 2026)
Cardiovascular disease remains the leading cause of death in Libya, accounting for approximately 37% of total mortality, according to the World Health Organization 2023 country profile [1]. Among these, acute coronary syndromes (ACS)—particularly ST-elevation myocardial infarction (STEMI)—represent a time-critical condition where survival is directly dependent on rapid access to reperfusion therapy. Yet in Libya, access to primary percutaneous coronary intervention (PCI), the gold-standard treatment, remains inconsistent, fragmented, and largely confined to a few urban centers. This gap is no longer simply a clinical issue—it is a national health system failure that demands urgent policy intervention.